Looking for home eaudiobook - Richardson, Arleta (christianaudio, 2016)
With his mother dead, his father gone, and his older brothers and sisters unable to help, eight-year-old Ethan Cooper knows it's his responsibility to keep him and his younger siblings together-even if that means going to an orphanage. Ethan, Alice, Simon, and Will settle into the Briarlane Christian Children's Home, where there's plenty to eat, plenty of work, and plenty of talk about a Father who never leaves. Even so, Ethan fears losing the only family he has. How can he trust God to keep him safe when almost everything he's known has disappeared? The first book in the Beyond the Orphan Train series, Looking for Home takes us back to 1907 Pennsylvania and into the real-life adventures of four children in search of a true home.